A Novel French-Style Salad Dressing Based on Pickering Emulsion of Oil-Water Lycopene from Guava and Cellulose Nanofibers - Catalina Gómez-Hoyos; Angélica Serpa-Guerra; Shaydier Argel. Pérez; Jorge Andrés Velásquez. Cock; Lina Vélez-Acosta; Piedad Gañán-Rojo; Robin Zuluaga-Gallego (Molecules)
The objective of this research was to assess the potential of a Pickering emulsion based on lycopene extracted from guava by sunflower oil-water and cellulose nanofibers (CNFs) isolated from banana residues as a novel ingredient for a French-style salad dressing. The aim was to determine the impact of this emulsion on the stability and rheological properties of the dressing as well as ascertain the presence of lycopene in the final product. The particle size distribution, rheological properties, and emulsion stability of the Pickering emulsion and salad dressing were evaluated. The sample exhibiting the optimal stability condition contained 0.5 wt.% of CNFs (EPI0.5). In order to prepare the French salad dressing based on this Pickering emulsion, three concentrations of vinegar were analyzed. All samples contained white salt and sugar. The findings suggest that alterations in emulsion stability may be influenced by the vinegar content and the presence of salt, particularly during the storage period, which also affects the concentration of lycopene. Notwithstanding these findings, the untrained panelists expressed a favorable opinion and acceptance of the dressings, indicating that the product could serve as an alternative means of enriching food through the incorporation of beneficial substances such as lycopene.